Assessment of tongue space area in a sample of Iraqi adults with class I dental and skeletal pattern - Kadhum, Mohammed A (Journal of Baghdad College of Dentistry, 2015)
Background: Lateral cephalometric radiography is commonly used as a standard tool in orthodontic assessment and treatment planning. This study aimed to determine the tongue and surrounding space area in a sample of Iraqi adults with class I dental and skeletal pattern. Materials and methods: The study included thirty healthy subjects (15 males and 15 females) with an age ranged between 23-34 years and class I dental and skeletal pattern with no history of any sleep related disorders. The assessed cephalometric measurement included length and height of the tongue and position of hyoid bone from cervical line. Descriptive statistics were obtained for the data. Genders difference was evaluated by independent sample t-test. Results: There were significantly higher values in males as compared to females in most of the measurements. Conclusions: The study provides preliminary details of tongue space area assessment in normal class I profile subjects. Keywords: Tongue space, lateral cephalometrics.